Nucleation and growth of mullite whiskers from lanthanum-doped aluminosilicate melts - Regiani, I; Magalhaes, WLE; de Souza, DPF; Paiva-Santos, C. O.; de Souza, M. F. (Amer Ceramic Soc, 2002)
Nucleation and growth of mullite whiskers in the La2O3-Al2O3-SiO2 system were investigated in the 1500degrees-1700degreesC temperature range. A differential thermal analysis (DTA) showed that the mullitization temperature decreases from 1350degreesC to 1240degreesC as a result of lanthania doping. In the temperature range of 1250-1500degreesC, most of the mullite grains have an Al2O3/SiO2 = 1.5 composition throughout the ceramic body; however, from 1400degreesC upward, the number of anisotropic grains with the Al2O3/SiO2 = 1.3 composition begins to increase. The concentration of alumina in the composition of the grain-boundary phase decreases as firing temperatures increase. At temperatures > 1500degreesC, alumina grains and whiskers grow on the internal and external surfaces of the ceramic body with the characteristic Al2O3/SiO2 = 1.3 composition. Removal of the mullite whisker layer by acid attack revealed an alumina-rich, rosace-like patterned microstructure correlated with the process of whisker nucleation and growth. In the early stages, whisker growth rates were found to be near 60 mum/h. Experimental evidence pointed to nucleation inside the thin glass layer on the external surface.